Pharmacogenomics in pediatric oncology: possibility to overcome drug-induced toxicity of anticancer treatment - Yu. V. Dinikina; E. N. Imyanitov; M. B. Belogurova; I. L. Nikitina (Лечащий Врач)
Background. Short-term and long-term toxicities of anticancer treatment are of increasing relevance, especially in children. Adverse events of anticancer treatment can cause mortality, organ toxicity of varying severity, subsequent disability, significant negative impact on psychosocial functioning and quality of life of patients and their families. This warrants the need for research on risk factors of drug-induced toxicity and new therapeutic approaches aimed to minimize the negative effects of anticancer and concomitant therapy, including new targeted drugs and immunotherapy. The development of human genome sequencing technologies and its integration into clinical practice, make possible treatment personification based on personal genetic variations. Pharmacogenomics, as a branch of pharmaceutics and pharmacology, plays a key role in predicting drug-induced toxicity and resistance to anticancer treatment in each patient. The main problem is the limited number of clinical studies in this area, small and heterogeneous cohorts of patients and the relative rarity of malignancies in childhood, that makes difficult to interpret obtained data and determine their clinical significance.Results. This article presents current literature data on clinically significant drug-gene associations and their therapeutic value on the safety and efficacy of anticancer therapy in pediatric patients, their diagnostic, therapeutic and prognostic value, as well as the opportunities of genome-guided managing treatment protocols, including option of rescue therapy.